Greenpeace, Corporations and Deforestation Crimes: A Case study of Hongkong Shanghai Bank Corporation (HSBC) in Indonesia - Karjaya, Lalu Puttrawandi; Satris, Rezki; Suspiati, Suspiati (Jurnal Hubungan Internasional, 2019)
As a political actor, non-governmental organizations have an essential role in the environmental sector. This paper aims to discuss the role of Greenpeace in driving HSBCâ€™s non-deforestation policy in Indonesia. To address deforestation in Indonesia, Greenpeace is pressing HSBC to stop funding and implement a â€œzero deforestationâ€ policy. In conducting the analysis, the researcher utilized the concept of NGOs and green theory. The concept of NGOs was used to classify Greenpeace as an organization and analyze the role of the organization in the process of making HSBCâ€™s non-deforestation policy. While the green theory was used to see the urgency of the problems of deforestation and the values championed by Greenpeace.